2014
DOI: 10.1016/j.tranon.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase-Type Plasminogen Activator Deficiency Promotes Neoplasmatogenesis in the Colon of Mice

Abstract: Urokinase-type plasminogen activator (uPA) participates in cancer-related biologic processes, such as wound healing and inflammation. The present study aimed to investigate the effect of uPA deficiency on the long-term outcome of early life episodes of dextran sodium sulfate (DSS)–induced colitis in mice. Wild-type (WT) and uPA-deficient (uPA−/−) BALB/c mice were treated with DSS or remained untreated. Mice were necropsied either 1 week or 7 months after DSS treatment. Colon samples were analyzed by histopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 80 publications
3
19
0
Order By: Relevance
“…Murine knockout models have demonstrated increased intravascular deposition of fibrin in adult mice that are deficient in tPA or uPA [125]. Deficiencies of uPA may also promote cancer progression in experimental models of inflammatory colon cancer [126]. In murine models, deficiency of TAFI has been linked with increased fibrin deposition and inflammation leading to liver damage [127].…”
Section: Congenital Defects and Variation In Fibrinolysismentioning
confidence: 99%
“…Murine knockout models have demonstrated increased intravascular deposition of fibrin in adult mice that are deficient in tPA or uPA [125]. Deficiencies of uPA may also promote cancer progression in experimental models of inflammatory colon cancer [126]. In murine models, deficiency of TAFI has been linked with increased fibrin deposition and inflammation leading to liver damage [127].…”
Section: Congenital Defects and Variation In Fibrinolysismentioning
confidence: 99%
“…The classification of small intestinal polyps according to the most advanced lesion they contained showed that “hygienic” T cell recipient mice had significantly more polyps bearing CIS compared to control mice [Fig 3b and 3c]. Lymphocytes, macrophages, neutrophils, plasmacytes and mast cells in the intestinal adenomas of both groups of Apc Min/+ mice followed the typical polyp-associated inflammatory cell topographical distribution pattern(23, 44). However, the inflammatory cell accumulation was more pronounced in the polyps of “hygienic” cell recipients.…”
Section: Resultsmentioning
confidence: 94%
“…Based on previously described histomorphological criteria (21, 43, 44) focal lesions of dysplasia/adenoma within polyps were identified as low-grade dysplasia (LGD) or high-grade dysplasia (HGD) and carcinoma in situ (CIS, intraepithelial neoplasia) [Fig 3a]. The classification of small intestinal polyps according to the most advanced lesion they contained showed that “hygienic” T cell recipient mice had significantly more polyps bearing CIS compared to control mice [Fig 3b and 3c].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations